Choices Women Make : Agency in Domestic Violence, Assisted Reproduction, and Sex Work - Showden, Carisa Renae (Book collections on Project MUSE., 2011)
Women's agency: Is it a matter of an individual's capacity for autonomy? Or of the social conditions that facilitate freedom? Combining theoretical and empirical perspectives, Carisa R. Showden investigates what exactly makes an agent and how that agency influences the ways women make inherently sensitive and difficult choices--specifically in instances of domestic violence, assisted reproduction, and sex work. In Showden's analysis, women's agency emerges as an individual and social construct, rooted in concrete experience, complex and changing over time. She traces the development and deploy.